The relationship between price earnings ratio, dividend yield, and Kuala Lumpur Composite Index towards OSK stock prices / Siti Haziqah Zulkefli - Zulkefli, Siti Haziqah (2011)
Stock prices is one of the most important indicator readily available to the investors for their decision to invest or not in a particular stock. Theories suggest that stock price changes is associated with changes in fundamental variables which are relevant for stock valuation like payout ratio, dividend yield, capital structure, earnings size of the firm and its growth. As one of the main purpose of this study is to examine the relationship between price earnings ratio, dividend yield and Kuala Lumpur Composite Index (KLCI) to the movement of OSK’s stock prices. Single linear regression and multiple regression analyses are used to explore the association between stock price changes and the variables. The data used consists of a monthly data from March 2006 to March 2011. A positive relation is found between price earnings ratio, KLCI and stock prices changes. However, a negative relation between dividend yield and stock prices changes. The paper supports the fact that stock valuation is relevant in determining stock prices changes for the of OSK Holdings Berhad.